The temperature-dependent expression of type II secretion system controls extracellular product secretion and virulence in mesophilic Aeromonas salmonida SRW-OG1 - Yi, Xin; Chen, Yunong; Cai, Hongyan; Wang, Jiajia; Zhang, Youyu; Zhu, ZhiQin; Lin, Mao; Qin, Yingxue; Jiang, XingLong; Xu, Xiaojin (Frontiers in Cellular and Infection Microbiology, 2022)
Aeromonas salmonicida is a typical cold water bacterial pathogen causing furunculosis in many freshwater and marine fish species worldwide. In our previous study, the pathogenic A. salmonicida (SRW-OG1) was isolated from a warm water fish Epinephelus coioides was genomics and transcriptomics analyzed. Type II secretion system was found in the genome of A. salmonicida SRW-OG1, while the expressions of tatA, tatB, and tatC were significantly affected by temperature stresses. At the same time, sequence alignment analysis, homology analysis and protein secondary structure function analysis showed that tatA, tatB, and tatC were highly conservative, indicating that they had important biological significance among bacteria. In this study, by constructing the mutants of tatA, tatB, and tatC, we investigated the mechanisms underlying temperature-dependent virulence regulation in mesophilic A. salmonida SRW-OG1. According to our results, tatA, tatB, and tatC mutants showed significantly reduced adherence, hemolysis, biofilm formation, motility, virulence and extracellular enzymatic activities including amylase, protease, lipase, hemolysis and lecithinase. The genes affecting amylase, protease, lipase, hemolysis, and lecithinase of A. salmonicida SRW-OG1 were identified as cyoE, ahhh1, lipA, lipB, pulA, HED66_RS01350, HED66_RS19960, aspA, fabD, and gpsA, which were significantly affected by temperature stresses and mutant of tatA, tatB, and tatC. Together, these indicated that tatA was involved in the temperature-dependent pathogenicity of mesophilic A. salmonida SRW-OG1 by assembling TatBC complex to participate in extracellular secretion mechanism.